The influence of off-farm work on farm income among smallholder farm households in northern Ghana - Benjamin Tetteh Anang; Clever Kwasi Apedo (Cogent Economics & Finance, 2023)
AbstractIncome diversification is an essential livelihood strategy among small-scale farmers in low-income countries. Through income diversification, farmers can potentially invest off-farm earnings into their farm business to enhance productivity and income from farming. Conversely, working off-farm can lead to a labour-loss effect which can reduce farm performance. This study therefore assesses the effect of off-farm work (OFW) on farm income using data from 486 smallholder farmers in northern Ghana. An endogenous treatment regression model was used to assess the effect of diversifying income sources on farm income. The results showed that involvement in OFW enhanced farm income per acre by GH¢ 386. Other factors that enhanced farm income included years of formal education and access to extension services and input subsidy. Farmer group membership and household size however reduced farm income. The farm sector can therefore take advantage of the positive linkage with the non-farm sector to improve farm income levels of farmers. In this light, government’s rural industrialization policy should seek to provide more job opportunities outside the farm sector to enable smallholder farmers to take advantage of such opportunities to improve income from on-farm activities.